The effect of 8 weeks of whole body vibration training on static balance and explosive strength of lower limbs in physical education students - George Dallas; Alexandros Mavvidis; Paschalis Kirialanis; Sotiris Papouliakos (Palacký University Olomouc, 2017)
Background: It has been shown that whole body vibration training has an effect on strength and balance in athletes of various sports.Objective: The purpose of the study was to examine the effect of 8 weeks of Whole Body Vibration (WBV) training on static balance and explosive strength of the lower limbs, using two different training intensities vibration protocols.Methods: Eighty-three physical education students (age 19.39 ± 2.35 years) volunteered to participate in an 8-week WBV training. They were randomly divided into two groups with 30 sec and 60 sec duration of vibration exposure per exercise, total volume of exercise was the same for both groups. The explosive strength of the lower limbs was assessed by a squat jump and static balance by Balance Error Scoring System at the baseline (pre-test) and after 8 weeks of WBV training at 15 sec, 5, 10, and 15 min after the end of WBV exposure. A two-way ANOVA 2 × 5 (protocol × time) with repeated measures on both factors was used. Univariate analyses with simple contrasts across time were selected as post hoc tests.Results: Results showed a time × protocol interaction effect for static balance (p < .001) but not for the squat jump (p > .05). Furthermore, a time effect was found for the static balance and squat jump test. The 60 sec protocol had a greater percentage improvement compared to the 30 sec protocol in static balance (p = .003), whereas the 30 sec protocol was superior to the 60 sec protocol in explosive strength. However, the differences between the two protocols were not significant.Conclusion: WBV training had positive effects on static balance and explosive strength in physical education students. Balance and jump performance may benefit from WBV training. Therefore, WBV may be an effective training method for the improvement of static balance and lower limb strength.